Hubungan Self Efficacy Dengan Kualitas Hidup Pada Pasien Hipertensi Di Wilayah Kerja Puskesmas Rangas Kab. Mamuju Provinsi Sulawesi Barat - Manuntungi, Andi Ernawati (Barongko: Jurnal Ilmu Kesehatan, 2023)
Hypertension occurs when blood pressure is above 140/90 mmHg. Hypertension is a condition in which an abnormal and continuous increase in blood pressure across multiple blood pressure measurements is caused by one or more risk factors that are not properly involved in maintaining normal blood pressure. To find out the relationship between self-efficacy and quality of life of hypertension patients at the Rangas Health Center, Mamuju Regency. This study is a quantitative study with an analytic observational approach. The sampling technique used in this study was non-probability sampling using purposive sampling technique. The population in this study was 50 and the sample was 44 respondents. The instrument used was the GSE questionnaire to measure the Self Efficacy variable and the WHOQOL-BREF questionnaire to measure the quality of life variable. Based on the results of the Spearman Rho test using a computer program, it is said that there is a meaningful or significant relationship Sig. (2-tailed) p value = 0.005 < smaller than 0.05 or 0.01. The results obtained show a value of 0.005 which means that there is a fairly strong relationship between Self Efficacy and Quality of Life in Hypertension Patients because the value of r = 0.473 is located between 0.26 - 0.50. So statistically there is a meaningful or significant relationship between self-efficacy and quality of life in hypertension patients at the Rangas Health Center. There is High Self Efficacy in Hypertensive Patients with Good Quality of Life as many as 30 respondents 68.2% and Poor Quality of Life as many as 11 respondents 25.0%, while those with Moderate Self Efficacy in Hypertensive Patients with Good Quality of Life as many as 2 respondents 4.5% with Poor Quality of Life as many as 1 respondent 2.3% in Hypertensive Patients in the Rangas Mamuju Health Center Working Area.